Modelling and sustainability analysis of biorefineries using sugarcane lignocellulose to produce polyethylene, sorbitol, glucaric acid and levulinic acid at existing South African sugar mills - Kapanji, Kutemba Kaina (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.